КОРЕКЦІЯ ВПЛИВУ ВИЩИХ ГАРМОНІК ПІД ЧАС СИНХРОННОГО ДЕТЕКТУВАННЯ КВАЗІСИНУСОЇДАЛЬНИХ СИГНАЛІВ - Борщев, П.І.; Ламеко, О.Л.; Мельник, В.Г. (Інститут електродинаміки НАН України, Київ, 2026)
This article examines errors caused by the influence of higher harmonics during synchronous detection of step-approximated quasi-sinusoidal signals in electrical impedance meters and other devices. Numerical modeling of the synchronous detection process is performed in case of coinciding shapes of the input and reference detector’s signals. It is shown that when the number of approximation steps in the input and reference signals is equal, the dependence of the error on the phase of the input signal is periodic, with the period of error variation coinciding with the width of the signal step. An analytical expression is derived showing that the maximum error value decreases proportionally to the square of the number of signal approximation steps. Сhanging the shape of the reference signals of the detectors by varying the number of approximation steps is proposed to reduce the error. In this case, the error decreases proportionally to the square of the least common multiple of the numbers of steps in the input and reference signals. A combination of stage numbers that have no common factors are found to be an optional choice. It is demonstrated that the error under study can be reduced by several dozen times without narrowing the frequency range of the converted signals. An experimental determination of errors caused by the influence of higher harmonics was carried out, results of which confirmed the effectiveness of the proposed method for correcting these errors. References 13, figures 5, tables 3.